Hands-on Remote Guidebook - Reis, Pedro (2023)
The COVID-19-crisis is perceived as a ‘turning point’ regarding the use of technology in education and training and, connected to this, the need for high-quality digital content being readily available and affordable for learners and educators has been underlined. At the same time, there is interest in capacitating teachers for developing their own teaching contents – based on the hands-on remote scheme. This guidebook aims to assist teachers in doing so by laying out the general principles and theoretical background of this scheme. Transforming the teaching of hands-on experiments into the digital realm allows not only to improve the education situation for (vocational) students under any pandemic conditions but also allows a closer link between work at home and work at school. In addition, the approach seems likewise usefully in situations beyond the pandemic: The type of digital collaboration proposed can support international teams in their cooperation – and possibly save some air travel and CO2 emissions, especially in view of the climate crisis. The hands-on remote approach can also enable distance learning during local weather events - also an important consideration at this time, due to class cancellations and learning delays caused by Corona. Educators from other fields (e.g., out-of-school learning places as museums, science centers, or student laboratories) may as well be interested to create their own resources and develop new ideas based on the foundations laid in this project. This guidebook is made available in two versions – digital and printed – with the purpose of enhancing the visibility of the project and inspiring new users to apply the teaching modules and the project’s core idea of hands-on remote teaching in group settings. The dissemination of this guidebook in different events – teachers’ professional development initiatives, school information events and conferences – will ensure a long-term and flexible use of the material and ideas developed in the “Hands-on-Remote” project.